Wool felt-based hospital bedding for reducing pressure injury incidence: an integrated microstructural, mechanical, and clinical study - Heloisa Nazaré dos Santos; Samuel Gomes Gontijo; Thalita Felício Soares; Túlio Vinicius Oliveira Campos; Carlos Alberto Silva de Miranda; Nelcy Della Santina Mohallem; Gustavo Fóscolo de Moura Gomes; Artur Caron Mottin; José Henrique Martins Neto; Helan Xu (Textile Research Journal, 2026)
This study was an investigation of the influence of using wool felt-based hospital bedding as a way of preventing the incidence of pressure injuries in patients with high risk of developing them. The influence of the number of wash cycles on lipid content, morphology, and mechanical performance of wool felt-based bedding was studied. A combined approach was adopted, including Soxhlet extraction for lipid content analysis, mechanical testing (traction, stretching, and tearing), scanning electron microscopy, and a randomized clinical evaluation in hospitalized patients with high risk. Chemical testing showed a decreasing trend in lipids with the number of washes, reaching a final value of 0.13%. Clinical results showed that the use of wool felt bedding generated a lower incidence of pressure injuries compared with conventional polyester-based bedding (4.2% vs. 12.6%; p = 0.04), along with good patient acceptance. Scanning electron microscopy showed that washing promotes the reorganization of fibers, changing from an initial compact structure to a more open and porous configuration. Mechanical tests indicated that the material presents greater elongation and adequate behavior under tension and rupture stresses, contributing to load redistribution. In the tensile and elongation tests, maximum tensile stress ranged from 4.11 to 6.13 MPa and elongation from 21.8% to 48.9% in the transverse direction; in the longitudinal direction, values ranged from 2.04 to 5.71 MPa and from 21.8% to 48.9%, respectively, for the unwashed condition and after nine wash cycles. In the tear resistance test, strain values ranged from 100% to 166% in the transverse direction and from 54% to 149% in the longitudinal direction, for the unwashed condition and after nine wash cycles, respectively. Analyses of chemical, structural, and mechanical properties suggest that wool felt provides better adaptability to the skin–material interface, reducing localized pressure concentrations. The lipid extraction test showed a trend of decreasing lipid content with the number of washes, reaching a final value of 0.13%; however, the increased porosity (increase in volume) of the material may contribute to greater water adsorption from the environment and consequent skin hydration. Mechanical tests showed that transverse elongation of 50% can contribute to a more efficient entanglement of fibers, resulting in a greater ability to withstand tensile loads. These findings highlight the potential of the material for hospital bedding applications, contributing to pressure injury prevention and improved patient comfort.